2000
DOI: 10.1007/s005920070012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with the pyridoindole antioxidant stobadine on antioxidant state and ultrastructure of diabetic rat myocardium

Abstract: Consistent with the postulated role of oxidative stress in the etiology of late diabetic complications, pharmacological interventions based on biological antioxidants have been suggested. The aim of the present study was to investigate the effect of dietary supplementation with the pyridoindole antioxidant stobadine on the myocardial antioxidant status and ultrastructure of streptozotocin-diabetic rats. Diabetic male Wistar rats were fed for 32 weeks a standard diet or a diet supplemented with stobadine (0.05%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 0 publications
13
36
0
Order By: Relevance
“…Histochemical techniques used in our previous studies have shown heterogeneously reduced activities of some other enzymes involved in metabolic and energetic processes in the heart of diabetic and hypertensive rats [8,11,30] that may contribute to its dysfunction. In addition to enzyme histochemistry, our studies demonstrated that capillary endothelial cells revealed similar reversible and irreversible subcellular alterations in the myocardium of diabetic and hypertensive animals [8,11,30,37] manifested by thickening of basal membrane, diminished number of ribosomes and pinocytic vesicles, injured mitochondria and electrolucent nuclear chromatin, various density of cytoplasm together with endothelial cell swelling accompanied by luminal narrowing, diversity of capillary calibre, endothelial extravastion, branching of capillaries and pericapillary fibrosis. They represent structural form of endothelial dysfunction and seem to make up an integral part of degradation processes in capillaries and might contribute to accelerated disappearance of capillary endothelium.…”
Section: Discussionmentioning
confidence: 58%
“…Histochemical techniques used in our previous studies have shown heterogeneously reduced activities of some other enzymes involved in metabolic and energetic processes in the heart of diabetic and hypertensive rats [8,11,30] that may contribute to its dysfunction. In addition to enzyme histochemistry, our studies demonstrated that capillary endothelial cells revealed similar reversible and irreversible subcellular alterations in the myocardium of diabetic and hypertensive animals [8,11,30,37] manifested by thickening of basal membrane, diminished number of ribosomes and pinocytic vesicles, injured mitochondria and electrolucent nuclear chromatin, various density of cytoplasm together with endothelial cell swelling accompanied by luminal narrowing, diversity of capillary calibre, endothelial extravastion, branching of capillaries and pericapillary fibrosis. They represent structural form of endothelial dysfunction and seem to make up an integral part of degradation processes in capillaries and might contribute to accelerated disappearance of capillary endothelium.…”
Section: Discussionmentioning
confidence: 58%
“…Yet these substances failed to improve the functional recovery after ischemia/reperfusion. The anti-dysrhythmic properties of STB may be mediated by its potent antioxidant protective effect, already shown in previous studies (Stasko et al 1990;Stefek et al 2000;Kucharska et al 2000), while the HR-lowering effect seems also to be involved. Additional studies are to determine which other potential mechanisms of action come into play.…”
Section: Discussionmentioning
confidence: 56%
“…STB also prevented degenerative changes seen in diabetic sympathetic nerves of the vas deferens (Gunes et al 2005) and significantly reduced oxidative damage of kidney tissue as well as diabetes-induced proteinuria and albuminuria (Stefek et al 2002). Long-term treatment of diabetic animals with STB attenuated pathological changes in the diabetic myocardium by diminishing oxidative damage of myocardial tissue and reducing angiopathic and atherogenic processes in the myocardium Stefek et al 2000). These findings, along with the high oral bioavailability of STB, its toxic safety, as well as efficient detoxification pathways, render this drug a prospective agent in the prevention of late diabetic complications (for review see Juranek et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Wistar nondiabetic rats CoQ 10 is known to comprise 10-16% of the total amount of mitochondrial CoQ, while in diabetic rats this ratio is between 8-12%. However, the content of CoQ forms has been reported to significantly increase in diabetic rats (up to 2.5 fold) [75,76]. Treatment with PAMAM G4 suppressed the concentration of these antioxidants, typically elevated in diabetic rats, to levels relevant to non-diabetic animals [76]; which may be regarded as indicative that PAMAM G4 had the ability to suppress oxidative stress in experimental diabetes rats.…”
Section: Novel Applications Behind the Unknown Face Of Pamam Dendrimementioning
confidence: 99%
“…However, the content of CoQ forms has been reported to significantly increase in diabetic rats (up to 2.5 fold) [75,76]. Treatment with PAMAM G4 suppressed the concentration of these antioxidants, typically elevated in diabetic rats, to levels relevant to non-diabetic animals [76]; which may be regarded as indicative that PAMAM G4 had the ability to suppress oxidative stress in experimental diabetes rats. The increased antioxidant activity is likely triggered by persistent hyperglycaemic states as a response to oxidative stress in diabetes [33,72,73,75,76], while it normalizes when high glucose, and the associated postsynthetic modifications of proteins, become ameliorated with the administration of PAMAM G4.…”
Section: Novel Applications Behind the Unknown Face Of Pamam Dendrimementioning
confidence: 99%